LEGAL CONSEQUENCES OF CHILDREN OUTSIDE OF MARRIAGE AFTER CONSTITUTIONAL COURT DECISION NUMBER 46/PUU-VIII/2010 - Asrul Hamid; Defel Fakhyadi (Jurnal Cendekia Hukum, 2022)
Civil Code, Law Number 1 of 1974 concerning Marriage, and the Compilation of Islamic Law (KHI)is a legal rule that regulates the regulation of children outside of marriage and KHI is specifically for people who are Muslim. Therefore, the Constitutional Court Decision Number 46/PUU-VIII/2010 concerning the position of children out of wedlock is stipulated as a solution so that there is no legal dualism in society. The Constitutional Court's decision was determined when Aisyah Moechtar submitted a judicial review to the Constitution Court about constitutionality of Article 2 paragraph (2) and Article 43 paragraph (1) of Law no. 1 of 1974 concerning Marriage. This happens because of the legal meaning of the phrase "born out of wedlock," so that there are multiple interpretations of the position and legal this consequences. Research method is normative juridical research using statutory approach to then conducted in-depth analysis. With the issuance of the decision of the Constitutional Court, children out of wedlock have a civil relationship with their mother, their father and father's family if it can be proven by science and technology. It should be understood that the illegitimate child referred to in the decision is an illegitimate child resulting from a religiously legal marriage (siri marriage) but is not recorded in state documents and does not apply to illegitimate children resulting from adultery so that the clear legal consequences.